UNLOCKING THE POTENTIAL OF EXISTING BAMBOO SCAFFOLD CONNECTIONS: A COMPREHENSIVE REVIEW ON REUSABILITY - Hintsa G. GEBREMARIAM; Ermias A. AMEDE; Leule M. HAILEMARIAM (European Journal of Materials Science and Engineering)
Bamboo scaffolding is a sustainable alternative to traditional scaffolding materials due to its low carbon footprint, renewability, and strength. Reusable connections are crucial to optimize its sustainability benefits. This review provides a comprehensive overview of the reusability potential of existing bamboo scaffold connections, exploring different connection types, factors influencing reusability, benefits and challenges, and current research and development efforts. Several factors influence the reusability of bamboo scaffold connections, including the design of connections to accommodate mid-culm attachment of secondary components, which is challenging for many existing connection types. Reusing bamboo scaffold connections offers significant sustainability and cost-effectiveness benefits, reducing the demand for new materials and minimizing construction waste. Friction-tight lashing, the most popular and adaptable bamboo scaffold connection method together with mechanical connectors to alleviate problems in traditional friction-tight lashing, offers high reusability potential. More advanced mechanical connections, such as notched and pierced connections, are also being explored for their reusability potential. Ongoing research and development efforts focus on innovative approaches such as three-dimensional printing, parametric software, and glue bonding for custom joint systems to improve the reusability of bamboo scaffold connections. By addressing the challenges and leveraging ongoing research and development efforts, reusable bamboo scaffold connections can play a crucial role in sustainable construction practices.